POSTHEMORRHAGIC SHOCK MESENTERIC LYMPH IMPAIRS SPLENIC DENDRITIC CELL FUNCTION IN MICE. Issue 2 (28th February 2023) - Liu, Hua; Li, Jian-Feng; Zhang, Li-Min; Wang, Huai-Huai; Wang, Xu-Qing; Liu, Gui-Qing; Du, Hui-Bo; Jin, Yu-Jie; Xing, Li-Qiang; Zhao, Zi-Gang; Niu, Chun-Yu
ABSTRACT: Dendritic cell (DC)–mediated immune dysfunction is involved in the process of severe hemorrhagic shock that leads to sepsis. Although post–hemorrhagic shock mesenteric lymph (PHSML) induces immune organs injuries and apoptosis, whether PHSML exerts adverse effects on splenic DCs remains unknown. In this study, we established a hemorrhagic shock model (40 ± 2 mm Hg for 60 min) followed by fluid resuscitation with the shed blood and equal Ringer's solution and drained the PHSML after resuscitation. At 3 h after resuscitation, we harvested the splenic tissue to isolate DCs using anti-CD11c immunomagnetic beads and then detected the necrotic and apoptotic rates in splenocytes and splenic DCs. We also detected the levels of TNF-α, IL-10, and IL-12 in the culture supernatants and surface marker expressions of MHC-II, CD80, and CD86 of splenic DCs following LPS stimulation for 24 h. Second, we purified the DCs from splenocytes of normal mice to investigate the effects of PHSML treatment on cytokine production and surface marker expression following LPS stimulation. The results showed that PHSML drainage attenuated LPS-induced cell death of splenocytes and DCs. Meanwhile, PHSML drainage enhanced the DC percentage in splenocytes and increased the TNF-α and IL-12 production by DCs and the expressions of CD80, CD86, and MHCII of DCs treated by LPS. Furthermore, PHSML treatment reduced the productions of TNF-α, IL-10, and IL-12 and the expressions of CD80 and CD86 in normal DCs after treatment with LPS. In summary, the current investigation demonstrated that PHSML inhibited the cytokine production and surface marker expressions of DCs stimulated by LPS, suggesting that PHSML plays an important role in hemorrhagic shock–induced immunosuppression through the impairment of DC function and maturation.